The JDownloader Immune System for Continuous Deployment - Rechenmacher, Thomas; Riehle, Dirk; Weber, Michael (Proceedings of the 53rd Hawaii International Conference on System Sciences, 2020)
Continuous deployment can reduce the time from a source code change to a newly deployed application significantly. Increased innovation speed can make all the difference in a competitive market situation. However, deploying at high frequency requires high speeds of discovering bugs in the deployed software. Using the JDownloader file download manager as our example, we present a fitness model to evaluate a continuously deployed software during operation for expected behavior, present the design and implementation of a monitoring component, and evaluate the model and its implementation using data from JDownloader’s multi-million member strong user base. Our evaluation finds that there had been thousands of undetected bugs, and that newly created bugs can be detected and reported 16 times faster than before.<br
Keywords: Continuous delivery; continuous deployment; immune system